STUDENTS’ PERCEPTION ON THE USE OF EPISODEN APPLICATION IN SPEAKING ENGLISH - Hidayat, Yulia; Damanik, Emeliya Sukma Dara (TELL - US JOURNAL, 2025)
This study used descriptive qualitative research to investigate students' perceptions on the use of the episoden application in speaking English. A total of 31 students in 11-th grade at SMK Bandung 1 Bandar Setia were involved in this study. The students were asked to fill out a questionnaire and then 10 of them were randomly selected to be interviewed. Students' perceptions on the use of Episoden application were divided into three categories. The first category investigates students' perceptions on the use of Episoden application. The second category of students' perceptions of the benefits on the use of Episoden application. The third category investigates students' perceptions of the challenges on the use of Episoden application. The results of this study show that many students had a positive perceptions on the use of Episoden application and also the benefits on the use of Episoden application. Meanwhile, students' perceptions of the challenges on the use of Episoden applications received negative perceptions.